2012
DOI: 10.7314/apjcp.2012.13.4.1675
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Recommended Treatments for Early Invasive Breast Cancer: Decisions of Women Attending Surgeons in the Breast Cancer Audit of Australia and New Zealand

Abstract: Aim: The study aim was to determine the frequency with which women decline clinicians' treatment recommendations and variations in this frequency by age, cancer and service descriptors. Design: The study included 36,775 women diagnosed with early invasive breast cancer in 1998-2005 and attending Australian and New Zealand breast surgeons. Rate ratios for declining treatment were examined by descriptor, using bilateral and multiple logistic regression analyses. Proportional hazards regression was used in explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Twenty studies (22 articles) were included . Four of these have been included using also data reported in the Johnstone review .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty studies (22 articles) were included . Four of these have been included using also data reported in the Johnstone review .…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, five were cohort studies where the exposed and the nonexposed subjects came from the same population …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these challenges, patients with poor adherence may not receive the full benefit of treatment and may consequently experience suboptimal outcomes, poor survival rates, potential adverse events and increase cost burden related to hospitalization (Ruddy et al, 2009). A large Australian and New Zealand data reported that 3.4% women with early invasive breast cancer declined clinicians' treatment recommendations and 23.6% of them declined chemotherapy (Roder et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is amongst the five most common cancers and ranks first among cancers diagnosed in Iranian women, comprising 24.4% of all malignancies with the mean age ranging from 47.1 to 48.8 years (Ferlay et al, 2012;Roder et al, 2012). Although the incidence of breast cancer is still relatively low when compared with western countries (Iran: 23.65 per 100,000 and United States: 140.8 per 100,000 Caucasian women), the number of patients with newly diagnosed breast cancer are increasing (Harirchi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%